2022
DOI: 10.3389/fnins.2022.842814
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Dots Between Hypercholesterolemia and Alzheimer’s Disease: A Potential Mechanism Based on 27-Hydroxycholesterol

Abstract: Alzheimer’s disease (AD), the most common cause of dementia, is a complex and multifactorial disease involving genetic and environmental factors, with hypercholesterolemia considered as one of the risk factors. Numerous epidemiological studies have reported a positive association between AD and serum cholesterol levels, and experimental studies also provide evidence that elevated cholesterol levels accelerate AD pathology. However, the underlying mechanism of hypercholesterolemia accelerating AD pathogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 226 publications
0
10
0
Order By: Relevance
“…Hypercholesterolemia may play a role in the development of cognitive impairment through acceleration of the accumulation of amyloid beta peptides [80][81][82]. Park et al [83] demonstrated that hypercholesterolemia accelerated Aβ accumulation and tau pathology, which was accompanied by microglial activation and subsequent aggravation of memory impairment induced by Aβ25-35.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia may play a role in the development of cognitive impairment through acceleration of the accumulation of amyloid beta peptides [80][81][82]. Park et al [83] demonstrated that hypercholesterolemia accelerated Aβ accumulation and tau pathology, which was accompanied by microglial activation and subsequent aggravation of memory impairment induced by Aβ25-35.…”
Section: Discussionmentioning
confidence: 99%
“…There is now a considerable literature on how cholesterol and ApoE interact with Abeta synthesis and transport, APP metabolism, amyloid formation and tau phosphorylation (Michikawa, 2006;Carter, 2007;Popp et al, 2013;Allinquant et al, 2014;Gamba et al, 2015;Sun et al, 2015;Fanaee-Danesh et al, 2019;Loera-Valencia et al, 2019;Chew et al, 2020;Chai et al, 2021;Nanjundaiah et al, 2021;Wu et al, 2022). In general higher plasma and brain cholesterol and its metabolites correlate with higher brain Abeta levels and lower CSF Abeta levels (Reed et al, 2014;Iriondo et al, 2020).…”
Section: Myelin Injury Coupled With Cholesterol Dysmetabolism Contrib...mentioning
confidence: 99%
“…Increased dietary cholesterol intake promotes Abeta formation and AD pathology (Pappolla et al, 2003;Ghribi et al, 2006;Ismail et al, 2017;Liu et al, 2018;Wu et al, 2022) and tau hyperphosphorylation (Bhat and Thirumangalakudi, 2013;Park et al, 2013) and cognitive impairment (Umeda et al, 2012). Decreased cholesterol biosynthesis decreases γ-secretase activity and decreases Aβ generation (Kim et al, 2016).…”
Section: Dietary Cholesterol and Cholesterol Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition, recent research has shown that cholesterol is essential to brain synapses and the protection of the immune system against cancer. 3,4 But aberrant levels of cholesterol in blood have been linked to numerous diseases such as hypertension, hypolipoproteinemia, 5 anemia, 6 septicemia, 7 coronary heart disease, 8 arteriosclerosis, brain thrombosis and myocardial infarction. 9 In particular, hyperlipidemia has been reported to be a major hidden danger of cardiovascular and cerebrovascular diseases.…”
Section: Introductionmentioning
confidence: 99%